Utilization Patterns of Antenatal Services Among Pregnant Women: A Longitudinal Study in Rural Area of North Karnataka. - C.S.Metgud; S.M.Katti; M.D.Mallapur; A.S.Wantamutte (Al Ameen Medical College, 2009)
Objectives: 1.To study the profile of antenatal care received 2. To know the factors influencing the utilization Study Design: Longitudinal study.Setting: Shindolli village of Belgaum District Participants: All women (n =130) in this village who were pregnant at the start of the study and who became pregnant during the study. Statistical Analysis: Proportions and Chi-square Test Results: Most of the pregnant women (92.31%) were registered for antenatal care, but only 30.00% of them were registered in the 1st trimester of pregnancy. As regards to TT immunization, 70.77% of the pregnant women had received 2 doses or 1 booster dose. Iron and Folic Acid supplementation was taken by 59.68% of the pregnant women. Nearly 39.52 % of pregnant women were provided with full antenatal care. The main antenatal care provider for pregnant women was doctor (64.52%). The provision of full antenatal care package was found to be significantly higher among the pregnant women belonging to social classes I and II and in those who have studied above SSLC. Conclusion: The study shows early and wide spread use of antenatal care, but it also reveals that the antenatal visits occur late in the pregnancy. The literacy of women has significant bearing on utilization of antenatal care by the pregnant women.